2022
DOI: 10.3389/frph.2022.820029
|View full text |Cite
|
Sign up to set email alerts
|

Historical Perspectives and Evolution of Menstrual Terminology

Abstract: Abnormal uterine bleeding (AUB) in the reproductive years in non-pregnant women comprises a group of symptoms that include abnormal frequency and the irregular onset of flow as well as prolonged and heavy menstrual bleeding. It is a common, chronic, and debilitating condition affecting women worldwide with an adverse impact on their quality of life. Until the last decade, the “menstrual” terminology used to describe both normal and abnormal uterine bleeding and its underlying causes was inconsistent, creating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…Avoid using terms such as menorrhagia, metrorrhagia, dysfunctional uterine bleeding, and oligomenorrhoea as they are ambiguous with no clear definition of what each term means (table 1). 25 This ambiguity may lead to mismatches in both clinical management and translation of research into clinical practice 6. AUB can be defined as chronic (present for more than 6 months) or acute.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoid using terms such as menorrhagia, metrorrhagia, dysfunctional uterine bleeding, and oligomenorrhoea as they are ambiguous with no clear definition of what each term means (table 1). 25 This ambiguity may lead to mismatches in both clinical management and translation of research into clinical practice 6. AUB can be defined as chronic (present for more than 6 months) or acute.…”
Section: Definitionsmentioning
confidence: 99%
“…Heavy menstrual bleeding alone comprises 20% of all referrals to gynaecological services in the UK,7 making it one of the commonest reasons that women are seen in primary and secondary care 1. Women often normalise their symptoms,6 but AUB can have a negative impact on all aspects of quality of life and is related to higher rates of work absence and unemployment 8. AUB can negatively affect a woman’s social, financial, emotional, and personal life as well as her work and relationships.…”
Section: Why Does It Matter?mentioning
confidence: 99%
“…For some, the experience of heavier bleeding was embarrassing. Research from the AUB field suggests that women often normalize their symptoms and do not seek help [ 6 ]; for example, in a European study, 46% of women sought no treatment or did not consult their doctor about their bleeding [ 7 ]. Interestingly, a recent survey of nearly 100 000 women focused on women’s health issues in the United Kingdom found that despite seeking help, 84% of women believed that there were times their concerns were not listened too by healthcare professionals [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…To systemize how women with AUB are evaluated, the vital step of improving and standardizing terminology used within the field was undertaken by FIGO after an extensive multistage process 28 . International consensus using a Delphi process was sought from 2005 onward, leading to the creation of the two FIGO systems for the assessment and classification of AUB 29 . By standardizing the descriptions of normal and abnormal menstrual function and the classification of causes of nongestational AUB in the reproductive years, communication regarding nongestational AUB can improve.…”
Section: The Value Of the Two Figo Systemsmentioning
confidence: 99%
“…28 International consensus using a Delphi process was sought from 2005 onward, leading to the creation of the two FIGO systems for the assessment and classification of AUB. 29 Nongestational AUB in the reproductive years can be either acute or chronic. Chronic AUB is defined by FIGO as: "bleeding from the uterine corpus that is abnormal in volume, regularity, and/or timing, and has been present for the majority of the past 6 months.…”
Section: Characterization and Classificationmentioning
confidence: 99%